Non Integer Identification of Rotor Skin Effect in Induction Machines - Abdelhamid Jalloul; Khaled Jelassi; Jean-Claude Trigeassou (Institute of Advanced Engineering and Science, 2013)
Fractional identification of rotor skin effect in induction machines is presented in this paper. Park‘s transformation is used to obtain a system of differential equations which allows to include the skin effect in the rotor bars of asynchronous machines. A transfer function with a fractional derivative order has been selected to represent the admittance of the bar by the help of a non integer integrator which is approximated by a J+1 dimensional modal system. The machine parameters are estimated by an output-error technique using a non linear iterative optimization algorithm. Experimental results show the performance of the modal approach for modeling and identification.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2286